Habilidades motrices y el desarrollo del lenguaje oral en estudiantes de nivel inicial de la Institución Educativa César Calvo de Araujo de Yurimaguas 2024 - Silva Alvarez, Ruth Erika (2024)
The objective of the study was to determine the relationship between motor skills and the development of oral language in initial level students of the César Calvo de Araujo educational institution in Yurimaguas in 2024. The research was basic, with a non-experimental design of scope correlational. The observation technique was used with a motor skills and oral language guide as an instrument. The population and sample were made up of 48 initial level students. The results confirmed a strong, direct and positive relationship between motor skills and the development of oral language, as well as its dimensions of form, content and use of language. with a Pearson coefficient r=0.937. This relationship was corroborated by the Student t test, which yielded a t value = 18.192 and a p-value = 0.000. In conclusion, it was determined that there is a significant relationship between motor skills and the development of oral language in the initial level students of the educational institution analyzed.